Analysis of Problematics and Ability to Understand Algebraic Mathematical Concepts of Class X High School Students - Faradilla, Hanifa; Putri, Rahmi; Gunawan, Rilla Gina (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This study employs a qualitative descriptive approach to explore high school students' understanding of algebraic concepts in Sungai Penuh City. The sample consists of 30 10th-grade students who were subjects of the study, assessed using a validated algebraic concept understanding test. The research process involved introducing the research objectives to the students and administering the test with adequate time. Data analysis was conducted descriptively to identify answer patterns, challenges faced by students, and the level of understanding of algebraic concepts demonstrated. Findings indicate significant challenges in students' mathematical concept comprehension, particularly in grasping basic concepts such as algebraic terms and the use of mathematical representations. To enhance students' understanding, it is recommended to implement a holistic learning approach that strengthens foundational concepts, integrates various mathematical representations, and provides direct problem-solving experiences. This research is expected to contribute to improving the effectiveness of mathematics education at the high school level.